2020
DOI: 10.1021/acs.jafc.0c05792
|View full text |Cite
|
Sign up to set email alerts
|

Novel Zn-Binding Peptide Isolated from Soy Protein Hydrolysates: Purification, Structure, and Digestion

Abstract: In this study, a novel Zn-binding peptide, Lys−Tyr−Lys−Arg−Gln−Arg−Trp (KYKRQRW), was purified and identified from soy protein isolate hydrolysates (SPIHs). The Zn-binding peptide exhibited improved Zn-binding capacity (83.21 ± 2.65%) than SPIH solutions. CD, NMR, and Fourier transform infrared spectroscopy were used to confirm the complexation between Zn and the peptide. The results showed that the Zn-binding peptide formed a folding structure with part of the β-sheet (29.3−13.4%) turning into random coils (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…These results suggested that SDDVL-zinc chelate had higher capacity to improve absorption and transportation of zinc in vivo than ZnSO 4 and zinc gluconate. Similar trend was obtained by previous studies (Sun et al, 2021;Zhu et al, 2021). The result in Figure 6f was consistent with the results in Figure 6c,e.…”
Section: Zinc Transportation Across Caco-2 Cellssupporting
confidence: 92%
See 2 more Smart Citations
“…These results suggested that SDDVL-zinc chelate had higher capacity to improve absorption and transportation of zinc in vivo than ZnSO 4 and zinc gluconate. Similar trend was obtained by previous studies (Sun et al, 2021;Zhu et al, 2021). The result in Figure 6f was consistent with the results in Figure 6c,e.…”
Section: Zinc Transportation Across Caco-2 Cellssupporting
confidence: 92%
“…Results of structure–chelating activity relationship analysis of oligopeptides demonstrated that the amino group and carbonyl group adjacent to the C‐terminal or N‐terminal of peptides played a key role in formation of peptide‐Zn complexes (Lihi et al., 2017). Especially, the γ‐carboxyl group (─COOH) in Glu or Asp was an effective zinc‐binding site because it can link with zinc through ionic bond (Zhu et al., 2021). In addition, several amino acid residues with specific groups can improve zinc‐binding ability of peptides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, Asp and Glu are acidic amino acids that can contribute more −COO to achieve chelation with Fe 2+ compared to neutral amino acids. These chelating abilities have been confirmed in Fe 2+ -binding peptides in whey protein hydrolysates and soy protein ( 34 , 36 ). Similarly, Arg, His, and Lys are basic amino acids that can provide −NH groups to combine with Fe 2+ ( 37 ).…”
Section: Discussionmentioning
confidence: 67%
“…The active peptides from natural sources, such as wheat, egg white, and soy, often carry trace elements with incredible functions ( 4 , 34 ). In this study, we chose pig skin as the chelating agent of Fe 2+ to obtain PSCP-Fe.…”
Section: Discussionmentioning
confidence: 99%